Transcatheter arterial embolization of acute bleeding as 24/7 service: predictors of outcome and mortality - Powerski, Maciej (Br J Radiol, 2018)
OBJECTIVE: To analyze times of occurrence and identify risk factors (RFs) for technical and clinical failure and mortality of transcatheter arterial embolization (TAE) of acute bleeding in a major hospital. METHODS: All TAEs performed at our hospital from 2006 to 2013 (n = 327) were retrospectively analyzed. RESULTS: TAEs were performed during regular weekday hours in 165 (50%) and during off-hours in 162 (50%) cases. With 40 regular and 128 off-hours/week, 3.25 times more TAEs were performed during regular hours. There was an even distribution across weekdays (Mon-Fri:16.9 ± 1.5%), while fewer TAEs were performed on weekends (Sat: 8.3%, Sun: 7.3%). Technical success of TAEs was 93.9% with a clinical success of 79.2% and a 30-day mortality of 18.4%. Shock was an RF for technical failure (p = 0.022). RFs for clinical failure were low hemoglobin (Hb) (p = 0.021) and transfusion of ≥6 units packed cells (p = 0.009). Independent RFs for mortality were clinical failure (p < 0.001), coagulopathy (p = 0.005), and shock (p < 0.001). CONCLUSION: Our results provide no evidence for a subjectively perceived increase in TAEs during off-hours but rather appear to show that most TAEs are performed during regular hours. Prompt TAE to control acute bleeding is crucial to prevent a drop in Hb with shock and the need for transfusion, which may promote coagulopathy and rebleeding, all of which are risk factors for a negative outcome. ADVANCES IN KNOWLEDGE: The presented analysis provides insights of occurrences and risk factors for success of transcatheter arterial embolization in acute bleeding in a large study population.